Factors Associated With The Incidence Of Toddler Obesity In The Outpatient Department Of Pediatrics, Dr. Sulaiman Alhabib Medical Center, Alnarjes, Riyadh, Saudi Arabia - Muslikhah Muslikhah; Muhammad Jauhar; Umi Farida (CV. AFDIFAL MAJU BERKAH, 2026)
Childhood obesity is a global health issue affecting individuals and communities, with serious disease risks such as diabetes and heart disease. This phenomenon is related to genetic, behavioral, environmental, and socioeconomic factors. In Saudi Arabia, the prevalence of childhood obesity reaches 82.49%, and in Riyadh, 32.5% of children under 12 years old are obese. Several contributing factors to childhood obesity include maternal knowledge about nutrition, paternal nutritional status, history of exclusive breastfeeding, and parenting styles. This study aims to identify factors associated with obesity in toddlers at the Outpatient Department of Pediatric Dr. Sulaiman Alhabib Medical Center Alnarjes, Riyadh. This research is quantitative with an analytical survey design using a cross-sectional approach. The population studied consists of mothers with toddlers under 5 years old at the Outpatient Department of Pediatric Dr. Sulaiman Alhabib Medical Center Alnarjes, Riyadh, in January 2024, with an average of 50 toddlers per month. Samples were taken using total sampling, resulting in a total sample of 50 toddlers. This research was conducted in May 2024 using a questionnaire. Data analysis was performed univariately and bivariately using the chi-square test. The results show that the age group of 24-36 months is the largest, with 20 children (40%) of the total respondents. A total of 62% of toddlers are obese. There is a significant relationship between maternal knowledge (p=0.003), parental nutritional status (p=0.008), exclusive breastfeeding (p=0.020), and parenting style (p=0.007) with the incidence of obesity in toddlers. It is recommended that mothers and families improve their knowledge of nutrition and child health through appropriate education and outreach.